The Role of the Government Internal Supervisory Apparatus (APIP) in Improving the Quality of Local Government Financial Reports (a Case Study of the Tebing Tinggi City Inspectorate) - Fajarwati, Meilisa; Maisyarah, Renny (Action Research Literate, 2026)
This study aims to analyze the role of the Government Internal Supervisory Apparatus (APIP) in improving the quality of local government financial reports at the Tebing Tinggi City Inspectorate. This type of research uses a qualitative approach with a case study method. This research informant numbered 7 people consisting of one structural official (Assistant Inspector of Government Affairs I), one middle auditor, one junior auditor, and four first auditors. Data collection techniques used in this study were interviews, observations, and documentation studies. The results of the study indicate that APIP plays an important role in improving the quality of financial reports through the implementation of financial report reviews, the implementation of the government internal control system (SPIP), and follow-up on audit recommendations. The increased role of APIP contributed to the acquisition of an unqualified opinion from the Supreme Audit Agency (BPK) consecutively for the past 7 years.